Doing and Undoing Gender in the nursery: a video analysis of the interactions of early childhood educators with children - Vogt, Franziska; Nentwich, Julia; Tennhoff, Wiebke (Swiss Journal of Educational Research, 2018)
Many children experience nurseries as the first institutional, educational setting, therefore they are relevant for ensuring gender equality. Four Swiss nurseries were visited for an ethnographic, video-based study in order to examine how gender is made relevant in the day-to-day practices of early childhood educators. The video data was analysed looking at the sequence of interaction between child and educator in terms of doing and undoing gender, as well as dramatizing and de-thematising. The results of the video study indicate that early childhood educators enhance the behaviour of the children, be it doing or undoing gender. Reactions seeking to enhance gender equality and challenging doing gender are however rare. In order to foster gender equality in nurseries, the organisational culture and quality are paramount.